A Course on Integral Equations with Numerical Analysis Advanced Numerical Analysis - Allahviranloo, Tofigh; Esfandiari, Armin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book suggests that the numerical analysis subjects$1 (Bmatter are the important tools of the book topic, because numerical errors and methods have important roles in solving integral equations. Therefore, all needed topics including a brief description of interpolation are explained in the book. The integral equations have many applications in the engineering, medical, and economic sciences, so the present book contains new and useful materials about interval computations including interval interpolations that are going to be used in interval integral equations. The concepts of integral equations are going to be discussed in two directions, analytical concepts, and numerical solutions which both are necessary for these kinds of dynamic systems. The differences between this book with the others are a full discussion of error topics and also using interval interpolations concepts to obtain interval integral equations. All researchers and students in the field of mathematical, computer, and also engineering sciences can benefit the subjects of the book.s
Introduction to Numerical Analysis -- Interval interpolation -- Orthogonal polynomials and Least square approximation -- Integral equations -- Numerical methods for Integral equations -- Numerical methods for Integral-differential equations -- Introduction to Interval Integral equations.
Keywords: Engineering mathematics; Mathematics$1 (BData processing.s; Engineering Mathematics; Computational Science and Engineering; Integral equations; Numerical analysis